2020
DOI: 10.1038/s41598-020-71564-z
|View full text |Cite
|
Sign up to set email alerts
|

Schisandrin B regulates MC3T3-E1 subclone 14 cells proliferation and differentiation through BMP2-SMADs-RUNX2-SP7 signaling axis

Abstract: Schisandrin B (SchB) is the highest content of biphenyl cyclooctene lignans in Schisandra chinensis. It has been reported to have a variety of pharmacological effects, including anti-inflammatory, anti-oxidant, anti-cancer, heart protection, liver protection. In this study, we found that SchB can promote the proliferation of MC3T3-E1 subclone 14 cells. Meanwhile, we found that SchB can regulate the BMP2-SMADs signaling pathway by increasing gene and protein expression of those relative biomolecules. Furthermor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…The anti-cancer activity of α-cubebenoate isolated from S. chinensis fruit was determined as previously described for gomisin J [ 25 ]. Additionally, α-cubebenoate used in this assay was decided based on the results of previous studies on the anti-obesity activity of α-cubebenoate and the anti-cancer activity of gomisin A [ 13 , 23 ]. Briefly, the two cell types were evenly seeded at a density of 7 × 10 3 cells/200 μL in RPMI 1640 and grown in a 5% CO 2 incubator for 24 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The anti-cancer activity of α-cubebenoate isolated from S. chinensis fruit was determined as previously described for gomisin J [ 25 ]. Additionally, α-cubebenoate used in this assay was decided based on the results of previous studies on the anti-obesity activity of α-cubebenoate and the anti-cancer activity of gomisin A [ 13 , 23 ]. Briefly, the two cell types were evenly seeded at a density of 7 × 10 3 cells/200 μL in RPMI 1640 and grown in a 5% CO 2 incubator for 24 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…The anti-cancer activities of schisantherins A, B, and C, gomisins A, B, and N, deoxyschisandrin, and α-iso-cubebenol derived from S. chinensis have been shown to induce apoptosis, suppress cell cycle arrest, and inhibit the proliferations of various cancer cells, including those of breast, colon, and ovarian cancer and hepatic carcinoma [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. However, other compounds present in S. chinensis including α-cubebenoate, cubebene, gomisin C, D, E, F, G, K3, and J have not been evaluated for anti-cancer activity in mammalian cells.…”
Section: Introductionmentioning
confidence: 99%
“…Conditional Smad4 KO mice (Dmp1-Cre;Smad4fx/fx) led to dentin defects, with wide predentin, thin dentin, disorganized dentin tubules, and decreased expression of Bsp, Collα1, Dmp1, and Dspp genes exhibited [ 156 ]. Canonical Smad signaling enhanced dental mesenchymal cell differentiation and Dspp expression via the action of Dlx5, Msx2, Osx, Runx2, Smads, and other compounds [ 92 , 157 , 158 , 159 , 160 ].…”
Section: Bmp Downstream Gene Expression During Tooth Developmentmentioning
confidence: 99%
“…Various in vitro and in vivo studies have found them to demonstrate various antioxidative, anti-inflammatory, anticancer, and antiviral properties, among others. For example, S. chinensis has an inhibitory effect on cytochrome P450, family 3, subfamily A (CYP3A), and P-glycoprotein (P-gp), which can mediate metabolism or efflux of substrates, and may interact with many drugs [ 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. In addition, Nasser et al [ 9 ] described various biological properties of schisandrin B.…”
Section: Introductionmentioning
confidence: 99%